Analyses of phenotypic differentiations among South Georgian Diving Petrel (Pelecanoides georgicus) populations reveal an undescribed and highly endangered species from New Zealand. - Johannes H Fischer; Igor Debski; Colin M Miskelly; Charles A Bost; Aymeric Fromant; Alan J D Tennyson; Jake Tessler; Rosalind Cole; Johanna H Hiscock; Graeme A Taylor; Heiko U Wittmer (PLoS ONE)
Unresolved taxonomy of threatened species is problematic for conservation as the field relies on species being distinct taxonomic units. Differences in breeding habitat and results from a preliminary molecular analysis indicated that the New Zealand population of the South Georgian Diving Petrel (Pelecanoides georgicus) was a distinct, yet undescribed, species. We measured 11 biometric characters and scored eight plumage characters in 143 live birds and 64 study skins originating from most populations of P. georgicus, to assess their taxonomic relationships. We analysed differences with principal component analyses (PCA), factorial ANOVAs, and Kruskal-Wallis rank sum tests. Results show that individuals from New Zealand differ significantly from P. georgicus from all other populations as following: 1) longer wings, 2) longer outer tail feathers, 3) deeper bills, 4) longer heads, 5) longer tarsi, 6) limited collar extent, 7) greater extent of contrasting scapulars, 8) larger contrasting markings on the secondaries, 9) paler ear coverts, 10) paler collars, and 11) paler flanks. Furthermore, we used a species delimitation test with quantitative phenotypic criteria; results reveal that the New Zealand population of P. georgicus indeed merits species status. We hereby name this new species Pelecanoides whenuahouensis sp. nov. Due to severe reductions in its range and the very low number of remaining birds (~150 individuals limited to a single breeding colony on Codfish Island/Whenua Hou) the species warrants listing as 'Critically Endangered'. An abstract in the Māori language/Te Reo Māori can be found in S1 File.